Photocatalytic activities of silver compound modified activated carbon@ZnO: Novel ternary composite visible light-driven photocatalysts - Pongsaton Amornpitoksuk (2018)
© 2018 Novel ternary photocatalysts composed of silver compound (SC), activated carbon (AC), and zinc oxide (ZnO) were prepared via the deposition of silver compounds; AgCl, AgBr, AgI and Ag3PO4on the surface of flower-like AC@ZnO. The photocatalytic experiment of the degradation of methylene blue and reactive orange under visible light irradiation showed that the ternary composite of SC/AC@ZnO was more active than AC@ZnO and ZnO. The results of an inhibitory activity experiment using scavengers confirmed that the superoxide anion radical is the main reactive species of the system.